Effects of Ferrous Iron Toxicity on Agronomic, Physiological, and Quality Indices of Flue‐cured Tobacco. (1st September 2019) - Li, Yan; Ren, Ke; Zou, Congming; Xie, Jiawei; He, Xian; Chen, Yi; Hu, Binbin; Shen, Junru; Hu, Xiaodong; Chen, Jie; Xia, Zhenyuan; Wu, Yuping; et al.
Abstract : Ferrous iron (Fe 2+ ) toxicity would cause flue‐cured tobacco ( Nicotiana tobacum L.) leaf browning, leading to yield loss and low quality. To explore the mechanism of leaf browning by Fe 2+, two flue‐cured tobacco varieties, Honghuadajinyuan (Hongda) and K326, were planted in pots with two different soil types. Ferrous iron with a concentration gradient of 0, 170, 340, 510, and 680 mg kg −1 soil were arranged. Three types of indicators—agronomic traits, physiological indices, and economic indices—of flue‐cured tobacco were investigated. With increasing concentration of applied Fe 2+, indices including plant height, biomass and chlorophyll content of the two varieties decreased, while browning scale increased. Activities of enzymes, including superoxide dismutase (SOD), tricarboxylic acid, and ascorbate peroxidase (APX) first increased and then decreased. Relative electrical conductivity and malonaldehyde (MDA) content gradually increased with concentration of applied Fe 2+ . Peroxidase (POD) activity and MDA content of K326 increased with Fe 2+ concentration. For Hongda, POD activity first increased and then decreased in sandy soil, while it continuously rose in red soil. The Fe 2+ content in each part of plants increased with increasing Fe 2+ concentration, while yield and average price decreased. This study demonstrated that applied concentration of Fe 2+ in soils affected agronomic traits and economic traits of flue‐cured tobacco by adjusting activities of SOD, CAT, APX, POD enzymes and MDA content. Consequently, understanding of physio‐biochemical responses of tobacco under Fe 2+ stress would be helpful to develop agronomic strategies to alleviate leaf browning and could be used as bio‐markers for Fe 2+ tolerance in breeding as well. Core Ideas Fe 2+ affected tobacco traits via activities of SOD, CAT, APX, POD enzymes, and MDA content. In two soils, ferrous ion stress caused reduced plant height, biomass, and chlorophyll contents. Soil type, variety (K326 and Hongda), and iron concentration together affected browning scale. Regarding oxidordeuctase activity, Hongda was suited to fine sand and K326 variety to red soil. The varieties had similar leaf weight, average price, and yield; these indices declined with increased Fe 2+ .